Konsep dan Implementasi Corporate Social Responsibility Berbasis Kearifan Lokal Indonesia : Sebuah Tinjauan Literatur - Riska Nur Rosyidiana; Ni Luh Putu Normadewi Abdi Pradnyani; Novrys Suhardianto (Akuntansi : Jurnal Akuntansi Integratif, 2023)
Corporate social responsibility (CSR) was just formally established in Indonesia by Limited Liability Companies Law Number 40 of 2007. The fundamental principles of CSR, on the other hand, are not new and can be interpreted through Indonesian local wisdom. The purpose of this research is to determine the concept and practice of CSR based on local wisdom that exists in Indonesia. This research can provide a comprehensive understanding in developing CSR strategies that have a positive impact on society and the environment, as well as maintaining the sustainability of the relationship between companies and local communities. To achieve its goals, this study reviewed 20 CSR articles based on local wisdom with an Indonesian background. To find relevant articles, this study evaluates the Scopus, Web of Science, and Google Scholar databases. This research focuses on the concept of CSR and its implementation in various Indonesian local cultures. According to the findings, CSR planning, implementation, and evaluation that considers local wisdom can lead to a sustainable CSR program. This research will also help future researchers conduct CSR research based on local wisdom by filling identified research gaps.